Short continuously reinforced concrete pavement design recommendations based on non-destructive ultrasonic data and stress simulation. - Salles, Lucio Salles de (2017)
Four sections of continuously reinforced concrete pavement (CRCP) were constructed at the University of São Paulo campus in order to introduce this kind of pavement structure to Brazil\'s technical transportation community. Sections were designed as 50 m long concrete slab, short in comparison to traditional CRCP, in order to simulate bus stops and terminals - locations of critical interest for public infrastructure. The thesis presented herein concludes this research project initiated in 2010. As the initial goal of this study was the development of coherent, reliable and intuitive design recommendations for the use of CRCP technology in Brazil, a profound understating of its structural and performance peculiarities was needed. For that, the cracking process of the experimental CRCP sections was recorded over a span of seven years. Due to the sections\' short length and lack of anchorage, the experimental \"short\" CRCP presented a cracking behavior quite different than traditional CRCP. There were much less visible cracks than expected. To address this issue, a novel technology in ultrasonic non-destructive testing of concrete structures was applied. Through ultrasonic signal interpretation it was possible to discover several incipient non-visible cracks within the slabs - many of these became apparent on the slab surface in later crack surveys - and to characterize visible and non-visible cracks regarding crack depth. The updated crack map with non-visible cracks showed similarities with traditional CRCP. Additionally, the ultrasonic data analysis provided important information on thickness variation, reinforcement location and concrete condition that were applied in theoretical simulations (finite element software) of the short CRCP. Simulations were attempted considering different slab geometries, firstly with transverse cracks as joints with high load transfer efficiency (LTE) and secondly with a continuous slab without cracks or joints. The latter simulation was more accurate reaching a shift factor between field and simulated stresses in the order of 0.7 to 1.0. Deflection data and LTE analysis from cracks and panels in between cracks further attested the slab continuous behavior, which contradicts current CRCP design models and performance predictors. Furthermore, critical traffic and environmental loading conditions concerning Brazil\'s climate and bus traffic characteristics were investigated and related using a selected fatigue model resulting in design recommendations in a chart format for the short CRCP aimed at long-term projects for over 20 years of operation. The design chart was successfully applied to investigate three failures presented by the experimental short CRCP due to thickness deficiencies pointed out by the ultrasonic testing.